Frontispiece: Cooperative Photochemical Reaction Kinetics in Organic Molecular Crystals. Issue 14 (10th March 2023) - Morimoto, Kohei; Kitagawa, Daichi; Bardeen, Christopher J.; Kobatake, Seiya
Abstract : Some organic molecules undergo cooperative photoreaction processes in crystals, which have received little attention. An appropriate understanding of the basic reaction process is important for a dynamic understanding of property changes. In this Review article, K. Morimoto et al. summarize multiple examples of photochemical reactions in the crystalline phase that do not follow classical kinetic behavior. They also discuss different theoretical methods that can be used to describe this behavior.